2001
DOI: 10.4049/jimmunol.166.6.3693
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of the B Cell Antigen Receptor into Lipid Rafts Reveals a Novel Step in Signaling

Abstract: The cross-linking of the B cell Ag receptor (BCR) leads to the initiation of a signal transduction cascade in which the earliest events involve the phosphorylation of the immunoreceptor tyrosine-based activation motifs of Igα and Igβ by the Src family kinase Lyn and association of the BCR with the actin cytoskeleton. However, the mechanism by which BCR cross-linking initiates the cascade remains obscure. In this study, using various A20-transfected cell lines, biochemical and genetic evidence is provided that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 40 publications
8
104
1
Order By: Relevance
“…In fact, the recruitment of CD40 into lipid rafts is shown not to require a specific CD40-induced signal because cytoplasmic tail-truncated CD40 molecules easily translocate into these microdomains. Similar findings were reported for other immune receptors such as BCR [35,36] and TCR [37,38]. Indeed, initial studies concerning the mechanism of BCR raft association showed that signalingincompetent mutant BCR translocated to lipid rafts upon receptor oligomerization suggesting that the signaling function of the BCR does not appear essential for translocation to lipid rafts [36].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In fact, the recruitment of CD40 into lipid rafts is shown not to require a specific CD40-induced signal because cytoplasmic tail-truncated CD40 molecules easily translocate into these microdomains. Similar findings were reported for other immune receptors such as BCR [35,36] and TCR [37,38]. Indeed, initial studies concerning the mechanism of BCR raft association showed that signalingincompetent mutant BCR translocated to lipid rafts upon receptor oligomerization suggesting that the signaling function of the BCR does not appear essential for translocation to lipid rafts [36].…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were reported for other immune receptors such as BCR [35,36] and TCR [37,38]. Indeed, initial studies concerning the mechanism of BCR raft association showed that signalingincompetent mutant BCR translocated to lipid rafts upon receptor oligomerization suggesting that the signaling function of the BCR does not appear essential for translocation to lipid rafts [36]. Consistent with this finding, the treatment of B cells with the Srcfamily kinase inhibitors, PP1 or PP2, failed to block BCR translocation [35,36].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…BCR signals as a consequence of concentrating BCR-associated Src family tyrosine kinases to promote their trans-phosphorylation and activation (39,40) and to promote localization of the BCR complex into liquid-ordered, cholesterol/glycosphingolipid-enriched compartments of the plasma membrane known as membrane rafts that contain high local concentrations of many of the positive regulators of the signaling cascade (41)(42)(43)(44)(45)(46). However, if pre-BCR signaling does drive B cell development in a ligandindependent fashion, it would suggest that pre-BCR signaling occurs independently of receptor aggregation.…”
Section: Electron Microscopic Analysis Of Primary Pro-b Cellsmentioning
confidence: 99%